2014
DOI: 10.3892/mmr.2014.1915
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone reduces ATDC5 chondrocyte cell viability by inducing autophagy

Abstract: Abstract. Prolonged use of glucocorticoids (GCs) for the treatment of chronic inflammatory and autoimmune diseases commonly exerts various side-effects, including impairment of skeletal development. However, the effect of GCs on chondrocytes, which play a key role in skeletal development, has been rarely reported. In the present study, autophagy was induced in the ATDC5 chondrocyte cell line following treatment with dexamethasone (Dex) at doses of 1-100 µM, and that this effect can be inhibited by RU486, a GC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…Several studies have focused on the relationship between glucocorticoids and autophagy. It is known that GCs are able to induce autophagy in different cell types [44,45], even though the explanation of the intimate molecular mechanism by which these drugs lead to this effect is not fully clear.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have focused on the relationship between glucocorticoids and autophagy. It is known that GCs are able to induce autophagy in different cell types [44,45], even though the explanation of the intimate molecular mechanism by which these drugs lead to this effect is not fully clear.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of other cell types with free DX has displayed different results though the reduction in viability has been clearly shown. [43][44][45] Other authors have reported the high cytotoxicity of DS loaded in PLGA/PEG scaffolds (1 mg per scaffold) in mouse primary calvarial osteoblasts, 46 as well as free DS in human microvascular endothelial cells at concentrations lower than ours (0.1 mM) 47 while other studies have revealed similar viability percentages at low concentrations (up to 100 mM) though showing differences between different cell lines displaying an enhanced toxic effect in somatic vs. tumor cells 48 or even at higher concentrations (3 mg mL À1 ) in primary rat embryo broblasts. 49 Cell membrane damage aer treatment with the considered subcytotoxic concentration (0.5 mg mL À1 ) of NPs or drugs was evaluated by ow cytometry through the distribution of viability, apoptosis and necrosis (Table 3).…”
Section: In Vitro Biocompatibility Studiesmentioning
confidence: 99%
“…Shen et al observed that DXM induced apoptosis in chondrocytes, and autophagy protected chondrocytes from glucocorticoids-induced apoptosis via ROS/Akt/FOXO3 signaling (24). Zhao et al also demonstrated that high doses of DXM reduce the ATDC5 chondrocyte cell viability by inducing autophagy (25). Therefore, in the current study, it is hypothesized that the degree of autophagy determines the protective or adverse role in DXM-induced cell injury.…”
Section: Discussionmentioning
confidence: 77%